Universal recurrence algorithm for computing Nuttall, generalized Marcum and incomplete Toronto functions and moments of a noncentral x2 random variable - Dias, J. C.; Nunes, J. P. V. (European Journal of Operational Research, 2018)
This article proposes a novel recurrence algorithm for computing Nuttall, generalized Marcum, and incomplete Toronto functions as well as truncated and raw moments (of any real order) for a noncentral x2 random variable. The numerical results highlight that the proposed recurrence method offers an excellent speed-accuracy trade-off for a wide variety of meaningful and relevant applications ranging from the operations management and industrial engineering fields to problems encountered in the financial engineering industry.